Chicken Sperm Cryopreservation: Review of Techniques, Freezing Damage, and Freezability Mechanisms - Yunhe Zong; Yunlei Li; Yanyan Sun; Gamal M. K. Mehaisen; Tianxiao Ma; Jilan Chen (Agriculture, 2023)
Ex situ preservation is an important method in the preservation of chickens, and cryopreservation of semen is the only method for gamete preservation at present. During the last two decades, many studies have been performed to develop standard chicken semen cryopreservation technology and achieve great progress. Many attempts and methods were investigated to adapt subspecies or different breeds. In this paper, we firstly reviewed the main factors affecting cryopreservation of chicken sperm, including the unique structure and characteristics of the spermatozoa. Secondly, the studies on key points of the chicken sperm cryopreservation technology, including semen dilution, cryoprotectants, equilibration time, packaging types, and freezing and thawing rates were summarized to generate the optimal parameters. Then, the mechanism underlying freezing damage and freezability revealed by recent omics methods relevant to the efficiency of cryopreservation were discussed. This review will provide relevant reference for the future investigation of poultry semen cryopreservation technology.